A study on the welfare of the animals in zoo negara / Liyana Muhd Fuad ...[et al.] - Muhd Fuad, Liyana; Akbar Khan, Azad; Khairudin, Mohd Khairul Azim; Mohamad Nizam, Muhammad Danial; Abdullah, Muhammad Faiz (2010)
In recent times, there have been many complaints made regarding the welfare of zoo animals by both the public and NGO's upon Zoo Negara. This forms the basis of the research in the light of animal suffering, standards of a zoo and the adequacies of the legislation and execution of laws. This paper sets out to examine the sufficiency of local laws and its enforcement in protecting the welfare of the animals of Zoo Negara as the national zoo of Malaysia. The primary legislation that provides for wildlife in Malaysia is the Protection of Wildlife Act 1972 which is only applicable in West Malaysia, which applies to the targeted area of research, Zoo Negara. Loopholes or shortcomings of the said Act are found throughout the research and has been affirmed by most of the people interviewed for the purpose of this paper. However, problems may surface as to the matter of jurisdiction or limitations of power to compel or take legal action on established zoos. Where rulings based on the old legislation may have been efficient in earlier days, it would be absurd to say the same for its implications 30 years down the road. At the time of research however, the writers were pleased to hear that the Act is soon to be revised. It has been said that the title in itself could be altered, with what is believed to be additional provisions and amendments supplying to a wider scope of laws. Therefore, it may be rightfully presumed that the current Protection of Wildlife Act is questionable and rather ineffective in its content and enforcement in providing protection of welfare for the zoo animals in Zoo Negara.